Simulating Facet‐Dependent Aggregation and Assembly of Mixtures of Polyhedral Nanoparticles. Issue 1 (17th October 2021) - Opletal, George; Barnard, Amanda S.
Abstract: The functionality of many nanomaterials involves the collective properties of aggregates and self‐assembled superstructures. Using the mesostructure as a design parameter requires predictive capabilities, but this is challenging when nanoparticle samples present a diverse mixture of shapes and surface facets. Molecular dynamics with over 5000 nanoparticles is used here to simulate different mixtures of polyhedral nanodiamonds, with surfaces indicative of their characteristic multipolar surface electrostatic potential. It is found that polydispersed samples have different aggregation behavior than monodispersed samples, particularly in regard to the interparticle coordination and degree of long‐range order, but mixing nanoparticle shapes does not affect aggregate porosity. Abstract : Mesoscale molecular dynamics reveals the order or disorder in nanodiamond samples depends on the mix of different shapes and the fraction of facets with different surface electrostatic potential.